2023
DOI: 10.3390/ijms241813976
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Beta Co-Pathology Is a Major Determinant of the Elevated Plasma GFAP Values in Amyotrophic Lateral Sclerosis

Andrea Mastrangelo,
Veria Vacchiano,
Corrado Zenesini
et al.

Abstract: Recent studies reported increased plasma glial acidic fibrillary protein (GFAP) levels in amyotrophic lateral sclerosis (ALS) patients compared to controls. We expanded these findings in a larger cohort, including 156 ALS patients and 48 controls, and investigated the associations of plasma GFAP with clinical variables and other biofluid biomarkers. Plasma GFAP and Alzheimer’s disease (AD) cerebrospinal fluid (CSF) biomarkers were assessed by the single molecule array and the Lumipulse platforms, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a meticulously designed study by Mastrangelo et al [1], an increase in plasma glial fibrillary acidic protein levels was observed in ALS patients compared to controls. This elevation was primarily attributed to concurrent Alzheimer's disease pathology, suggesting its potential as a reliable biomarker for cognitive impairment in ALS.…”
Section: Exploring Biomarkers In Neurological Disease Diagnosticsmentioning
confidence: 95%
“…In a meticulously designed study by Mastrangelo et al [1], an increase in plasma glial fibrillary acidic protein levels was observed in ALS patients compared to controls. This elevation was primarily attributed to concurrent Alzheimer's disease pathology, suggesting its potential as a reliable biomarker for cognitive impairment in ALS.…”
Section: Exploring Biomarkers In Neurological Disease Diagnosticsmentioning
confidence: 95%